1. The problem statement, all variables and given/known data Show that: ∇x(∇xB) = (B∇)B - ∇ (1/2B2) 2. Relevant equations r = (x,y,z) = xiei ∂xi/∂xj = δij r2 = xkxk δij = 1 if i=j, 0 otherwise (kronecker delta) εijk is the alternating stress tensor and summn convn is assumed. 3. The attempt at a solution On the LHS I simplified to get: εijk∂2/∂xj∂xk but was unsure what to do next because the RHS contains only first order derivatives On the RHS I was able to get to: (B∇)B - ∇ (1/2B2) = B(∂Bi/∂i)-B = B(∂Bi/∂i-1) I feel like I'm just not seeing some simple trick, or there is a rule that I don't remember/haven't learned. This is for my Classical Mechanics class BTW.